Perancangan Pet Furniture pada Ruang Keluarga - Rolivia John; Yusita Kusumarini; M. Taufan Rizqy (Intra, 2016)
Pet furniture is a furniture that adds a medium for pets to do activities with its owner. Pet furniture is designed by the need for compliance with daily activities of people who have pets that live in their home. People who have pets mostly do activities together with their pet inside their home to improve interaction and strengthening the bond between each other. The design of pet furniture is limited to cats and dogs, which are the most common animals that people kept as pets. The design method used is design thinking that prioritizes in facts collection related to the needs of space as a fundamental in designing pet furniture. The design of furniture that can accommodate human activities with the dogs and cats in the family room has been design processed it with the results of the design that applies the principles of the limitations on the design of pet furniture which include space user with pets, useing pallet scrap wood as the main material which is one of the potential waste in a production environment , as well as the use of knock-down system as a consideration for dogs and cats’ character that like to damage the furniture so that the detachment section can be replaced as needed.